Siedleckie rekolekcje (ks. bp Ignacy Świrski - prof. Stanisław Pigoń) - Kłak, Czesław (Wydawnictwo Uniwersytetu Rzeszowskiego, 2012)
The project of encoding Stanisław Pigoń’s correspondence has included letters exchanged between Professor Stanisław Pigoń (1885-1968) and Bishop Ignacy Świrski (1885-1968) in years 1933-1967. 75 letters written by Świrski and only 3 by Pigoń were preserved but they allowed to recreate the history of the friendship between the heroes of this story and even to reach deeper, beyond the cited and published in full letters, in order to answer the question: what cultural, historical and ideological circumstances brought those two individuals closer to each other and what values laid the foundations for their friendship?
Retreat in Siedlce (Bishop Ignacy Świrski – Professor Stanisław Pigoń)
Keywords: Świrski Ignacy; Pigoń Stanisław; epistolografia - XX w.; edytorstwo